ANALISIS HARGA JUAL DAN KONTRIBUSI PENDAPATAN USAHATANI JAGUNG MANIS TERHADAP PENGELUARAN RUMAH TANGGA PETANI DI DESA SAMBURAKAT KABUPATEN BERAU (Selling Price Analysis And The Contribution Of Sweet Corn Farming Income To The Expenditure Of Farmer Households Samburakat Village Gunung Tabur District, Berau Regency) - GALINGGING, HERWAN; HAQ, ARSYADANI SABILAL; VIRA, VIRA (Universitas Mulawarman (University of Mulawarman), 2025)
The objectives of this study are to: 1). Analyzing the amount of decent selling price of corn at the farmer level in Samburakat Village, Gunung Tabur District so that farmers get income equivalent to the MSE (Regency Minimum Wage) standard and per capita expenditure of household consumption of residents of Berau Regency (PKRT) and the Farmer Exchange Rate (NTP). 2). To find out the percentage of corn hustani income to meet the consumption expenditure of farmers' households based on each type of corn selling price that was formed previously. This research was conducted from December 2020 to February 2021 which is located in Samburakat Village, Gunung Tabur District. The data analysis method in accordance with the objectives used in this study includes; Analysis of the Selling Price Determination Method of Cost Plus Price, and the percentage contribution of corn farming income to farmers' household expenditures. The results of the study show that. The average selling price of corn based on the actual selling price, MSEs, household consumption expenditure, and the Farmer Exchange Rate (NTP) is Rp. 7,648.65.Kg-1, Rp. 9,300.95.Kg-1, Rp. 11,808.95.Kg-1 and Rp. 12,145.36.Kg-1. Only the selling price of corn based on NTP can meet 66.81% of the consumption expenditure needs of farmers' households with an average household of 2.57 people. after meeting the needs of farming capital for the next planting season.